Undergraduate Diagnostic Imaging Fundamentals - Burbridge, Brent; Mah, Evan (Open textbook library., 2017)
Diagnostic Imaging principles and concepts are augmented by the presentation of images for common clinical conditions. Guiding principles related to minimizing radiation exposure and requesting the most appropriate imaging examination are addressed.Static images are enhanced by the ability to access images stored and displayed on an Html-5 compatible, Dicom image viewer that simulates a simple Picture Archive and Communication system (PACS). Users can also access other imaging from the Dicom viewer (ODIN), beyond the basic curriculum provided, to further advance their experience with viewing diagnostic imaging pathologies.